COVID-19 risk perceptions among healthcare workers during early “new behavior norms” phase - Lolita Lolita; Azis Ikhsanudin (International Journal of Public Health Science (IJPHS), 2022)
The coronavirus disease 2019 (COVID-19) pandemic poses a serious health threat among Indonesian healthcare workers. As front-line workers, they were facing higher risk due to the prolonged exposure of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This study aimed to explore various factors affecting perceived risk among healthcare professionals. A cross-sectional study was conducted among health practitioners who met the inclusion criteria of being over the age of 17 years and resided in Indonesia. This study was conducted during the early "new normal behavior" period from April to July 2020. The sampling technique was convenience sampling which involved collecting data through the online questionnaire. The data were analyzed through the Spearman correlation method using SPSS version 22.0. A total of 248 respondents were included in the final analysis. Overall, age (p=0.017) and health status (p=0.001) significantly affected the COVID-19 risk perception among healthcare workers. Therefore, comprehensive COVID-19 risk communication should be established to optimize health behavior and crisis control management among healthcare workers.